Studi Awal Analisator Perubahan Sifat Elektrik Materi Cair yang Berinteraksi dengan Cahaya untuk Aplikasi Spektrometri - angga wahyu pratama; Arif Surtono; Junaidi Junaidi (Jurnal Teori dan Aplikasi Fisika, 2019)
An initial study research has been carried out on the realization of electrical properties analyzer of liquids that interact with light to be applied to spectrometry. This study aims to develop a spectrometry method based on changes in electrical resistance in liquids when interacting with laser. Methylene blue solution was used as a sample that illuminated by a laser with 650 nm wavelength.The laser beam causes a change in electrical resistance in the methylene blue solution detected by Arduino Nano and converted to a concentration quantity. The conversion equation for changes in electrical resistance to concentration was obtained from the measurement of the change in electrical resistance of methylene blue solutions at concentration of 100 ppm, 200 ppm, 400 ppm, 600 ppm, 800 ppm, 1000 ppm. The equation was obtained based on the exponential regression approach with error value of 15,70 %. The analyzer test was carried out by measuring the concentration of methylene blur solution at a concentration of 500 ppm, 600 ppm, and 700 ppm. The test results show an error value of 9,83 %.